Watershed development projects in India: an evaluation - Kerr, John M. (International Food Policy Research Institute, 2002)
In recent years India has looked to watershed development as a way to realize its hopes for agricultural development in rainfed, semi-arid areas. These areas were bypassed by the Green Revolution and have experienced little or no growth in agricultural production for several decades. By capturing scarce water resources and improving the management of soil and vegetation, watershed development has the potential to create conditions conducive to higher agricultural productivity, while conserving natural resources....This case study of watershed projects in Andhra Pradesh and Maharashtra, India, fits squarely into IFPRI's work on development strategies for less-favored lands -- areas where agroclimatic conditions are difficult or infrastructure and support services have been neglected. It offers important insights for IFPRI's research in other parts of the world, including work under way in the East African highlands, the hillsides of Central America, and the West Asia and North Africa regions. While much has been written about watershed development, there have been few efforts to systematically evaluate it. By doing so, John Kerr and his colleagues Ganesh Pangare and Vasudha Lokur Pangare contribute immensely to our understanding of the promise and challenges of watershed development... The authors conclude that while most of the projects they surveyed have had relatively little impact, those that take a more participatory approach and are managed by NGOs have in fact performed better in conserving natural resources and raising agricultural productivity. But such success may come at the expense of the poorest people in watershed areas because improving the management of a watershed usually requires restricting access to the natural resource base on which they depend. Many watershed development projects do not work because those whose interests are harmed refuse to go along with the effort. The authors argue that for watershed development to succeed on a large scale, projects must find a way for all affected parties to share in the net gains generated.